Hipnoterapi Terhadap Depresi Postpartum pada Ibu Primipara - Nengah Runiari; Nyoman Hartati; I Wayan Candra (Jurnal Gema Keperawatan, 2013)
The purpose of this study was to analyze the effect of hypnotherapy on primiparous tendency postpartum depression. The study design was a non-randomized group pretest-posttest design. Samples are 24 people primiparous mothers consisting of 12 people who were given hypnotherapy group and 12 people are not given hypnotherapy group. Sampling was done by quota sampling. The research was conducted on two places, namely Puskesmas Pembantu Dauh Puri and BPS Ni Wayan Suri. The instrument used to measure postpartum depression using the Edinburgh Postnatal  Depression Scale (EPDS), which has been modified by Soep. Results obtained chi square test p = 0.015 (0.005) indicating effect of hypnotherapy on tendency postpartum depression in mothers